CORRELATION AND COMPARISON OF SEAWATER δ34SSULFATE RECORDS AT THE PERMIAN-TRIASSIC TRANSITION - Gorjan P.; Kaiho K. (My University, 2007)
Correlation of carbonate-associated sulfate (CAS) δ34S-analysed Permian-Triassic (P-Tr) sections via conodont biostratigraphy and sequence stratigraphy shows distinct phases in the oceanic δ34Ssulfate evolution during the period ~ 1 million years (m.y.) either side of the P-Tr boundary. A δ34Ssulfate rise in the Changhsingian, prior to the end-Permian mass extinction, is followed by a period of about 350,000 years of erratic and substantial δ34Ssulfate movements (range = ~ + 1‰ to ~ + 28‰), the mass extinction occurring in the middle of this period. The sharp swings in this phase indicate severe changes in the oceanic sulfur geochemistry, and perhaps stages of ocean inhomogeneity. Low (< + 15‰) δ34Ssulfate values coincide with the mass extinction horizon, suggesting the extinction is related to an input of relatively 32S-enriched sulfur into the oceanic sulfate reservoir. The source of this sulfur most likely being H2S from euxinic waters. After the erratic δ34Ssulfate phase there is a stabilisation of δ34Ssulfate values (~ + 17‰) until the later Griesbachian. However, there is a possibility of discrepant Panthalassan and Tethyan data sets during the early to mid Griesbachian, but this requires further work for confirmation. δ34Ssulfate values are erratic in the late Griesbachian to early Dienerian, suggesting further perturbation of the sulfur cycle. The poorly age-constrained Smithian record shows a wide range of δ34Ssulfate values probably indicating swings during that time also. The δ34Ssulfate movements from the Changhsingian to Smithian indicate the Permian-Triassic transition is a time of intense changes in the sulfur fluxes to and from the oceans and perhaps stages of ocean inhomogeneity. © 2007.
Keywords: δ34S; BIOSTRATIGRAPHY; CAS; MASS EXTINCTION; PERMIAN-TRIASSIC; SULFUR ISOTOPES; Triassic; Permian; Mesozoic::Triassic; Мезозой::Триасовая; Paleozoic::Permian; Палеозой::Пермская